PELATIHAN PELAPORAN PAJAK SECARA ONLINE BAGI KARYAWAN PT BANGUN SUKSES LESTARI UNTUK TAHUN PAJAK 2024: PENINGKATAN KOMPETENSI DAN KEPATUHAN PAJAK DI ERA DIGITAL - Pahmi, Saepul; Pratiwi, Widia; Yuliartia, Dina (LPPM Institut Pendidikan Nusantara Global, 2024)
Online tax reporting via the e-filing system is now an obligation for taxpayers in Indonesia, including companies that have tax obligations. However, not all employees in companies understand well how to report taxes online. Therefore, online tax reporting training is very important to improve employee skills in carrying out tax obligations correctly. This program aims to provide training to PT BSL employees on effective ways to use the online tax reporting system, as well as increase their awareness of the importance of tax compliance. In implementing this program, the PKM team carried out training activities which included an introduction to the e-filing system, practice filling out SPT, as well as outreach regarding the latest tax regulations. The expected result is increased employee understanding of online tax reporting and maintained tax compliance in the company.